BUREAUCRATIC TRANSFORMATION WITH ENTREPRENEURIAL SPIRIT IN THE PUBLIC SERVICE SECTOR TO MEET THE NEEDS OF THE COMMUNITY AS CUSTOMERS - Arlis Prayugo; Rahadi Budi Prayitno; Jovan Prima Firmansyah; Wahyudi Pramono (Jurnal Scientia, 2023)
The nature of the government is a servant to the people. Continual improvement of the public service sector in the government bureaucracy should indeed be done. This is an embodiment of good governance to answer challenges to the needs of the community in achieving clean, good and authoritative governance (clean and good governance). Restructuring must be accompanied by the development of a new bureaucratic value system and culture, which places citizens at the center of bureaucratic life and is able to lay the foundation for development and professionalism in the bureaucracy. Bureaucracy and its apparatus must be able to play an active role in realizing democratic values ​​of governance such as participation, transparency, and accountability to the public. The characteristics of public bureaucracy that tend to dominate the policy-making process and hinder public involvement in that process must be removed. Public bureaucracy must be more open and actively involve its citizens in government activities and public services.